2020
DOI: 10.29271/jcpsp.2020.07.701
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Estimated Glomerular Filtration Rate with Both Serum Creatinine and Cystatin C (eGFRcr-cys) versus Single Analyte (eGFRcr or eGFRcys) Using CKD-EPI and MDRD Equations in Tertiary Care Hospital Settings

Abstract: Objectives: To assess and compare the glomerular filtration rate (eGFR) estimated through MDRD and CKD-EPI cr equations in early and late stages of chronic kidney disease on biochemical marker creatinine (eGFR cr ), cystatin C (eGFR cys ); and combined (eGFR cr-cys ), using CKD-EPI equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The CKD-EPI working groups also have explained the above factor, indicating that the errors due to non-GFR determinants of serum creatinine and cystatin-C are independent and smaller in the combined equation. This was further strengthened by the findings of Khalid et al (2020), which revealed a strong correlation between the creatininecystatin-C combined eGFR equation, which will be useful in the clinical diagnosis of patients with CKD.…”
Section: Methodsmentioning
confidence: 89%
“…The CKD-EPI working groups also have explained the above factor, indicating that the errors due to non-GFR determinants of serum creatinine and cystatin-C are independent and smaller in the combined equation. This was further strengthened by the findings of Khalid et al (2020), which revealed a strong correlation between the creatininecystatin-C combined eGFR equation, which will be useful in the clinical diagnosis of patients with CKD.…”
Section: Methodsmentioning
confidence: 89%
“…In the study, the glomerular filtration rate was assessed by the most updated CKD-EPI formula, as it better describes renal filtration, especially in lower stages (G1 and G2) of chronic kidney disease [ 13 , 14 , 15 ]. We have found that the first administration of radioisotope therapy resulted in no change in glomerular filtration in the whole study group.…”
Section: Discussionmentioning
confidence: 99%